Analysis of the clinical efficacy and safety of anti‐PD‐1 immune checkpoint inhibitors in locally advanced nasopharyngeal cancer - Shuling Shi; Bingyan Li; Pengcheng Zhou; Linhui Chen; Huizhen Li; Yingyi Wang; Xiaoyu Deng; Qianqian Dang; Jingjing Wu; Boya Zha; Peihong Li; Yingjuan Zheng; et al. (Cancer Medicine)
Abstract Objective To analyze the efficacy and adverse effects of anti‐PD‐1 immune checkpoint inhibitors aimed at nasopharyngeal carcinoma (NPC). Methods During the first stage of the study, using 40 patients with stage III/IVa NPC treated with anti‐PD‐1 immune checkpoint inhibitors in combination with chemoradiotherapy as a first‐line treatment (observation group) and 70 patients with NPC treated with chemoradiotherapy alone (control group). In the second stage of the study, 88 patients with NPC treated with immune checkpoint inhibitors were grouped according to the number of lines of immunotherapy, the number of times, and the types of application. Results Observation of the short‐term effects in the first stage indicated that the objective response rate (ORR) of the observation group and the control group against primary foci of NPC was 75.0% versus 40.0%; the mortality rate of the observation group was much lower than that of the control group. The overall first‐line treatment evaluation of the observation vs. control groups were as follows: ORR (67.5% vs. 38.6%); median PFS (17.52 vs. 17.21 months); and median OS (18.68 vs. 18.14 months), respectively (p < 0.05). The second stage of the study had an ORR of 53.4%, and the efficacy of immunotherapy was related to staging, timing, and frequency. Conclusion Anti‐PD‐1 immune checkpoint inhibitors combined with chemoradiotherapy as the first‐line treatment for nasopharyngeal carcinoma may improve patient outcomes significantly. Timing, frequency, and the type of immunotherapy exerted an effect on the efficacy of immunotherapy. Adverse effects that occurred during treatment were tolerable and controllable.